Determining factors of sustainability report using the institutional isomorphism theory approach - Tri Siwi Nugrahani; Hadri Kusuma; Johan Arifin; Rifqi Muhammad (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
One form of company participation in sustainable development is the preparation of quality reports (SR) taking into account SR content and pressure from stakeholders including the determinants of SR quality in companies listed on the IDX during 2017-2020 with an isomorphism theory approach. The sample for this study was 444 companies using the purposive method, with the criteria for companies compiling SRs during the year of observation either separately or in combination with the annual financial statements. Data analysis with multivariate regression. The results showed that environmental pressure and social pressure coercively isomorphism had an effect on SR quality, and industrial pressure had mimetic isomorphism affected SR quality, while normative pressure from the audit committee had no effect on SR quality because p > 0.05. This study proves that testing the quality of SR with a coercive, mimetic, and normative isomorphism theory approach can determine the quality of SR.